Marketing 3.0 : from products to customers to the human spirit - Kotler, Philip; Kartajaya, Hermawan, 1947-; Setiawan, Iwan (John Wiley & Sons, 2010)
Understand the next level of marketing The new model for marketing-Marketing 3.0-treatscustomers not as mere consumers but as the complex, multi-dimensional human beings that they are. Customers, in turn, are choosing companies and products that satisfy deeper needs forparticipation, creativity, community, and idealism. In Marketing 3.0, world-leading marketing guru PhilipKotler explains why the future of marketing lies in creatingproducts, services, and company cultures that inspire, include, andreflect the values of target customers. Explains the future of marketing, along with why most marketersare stuck in the pastExamines companies that are ahead of the curve, such as S.C. JohnsonKotler is one of the most highly recognized marketing gurus, famous for his "4 P's of Marketing" In an age of highly aware customers, companies must demonstratetheir relevance to customers at the level of basic values. Marketing 3.0 is the unmatched guide to getting out front ofthis new tide sweeping through the nature of marketing.